MARKING THE MODERN CHALLENGES OF PUBLIC-PRIVATE COOPERATION IN THE AREA OF SECURITY - Komarčević, Miodrag; Živanović, Cvijetin; Arnautović, Ivan (ACADEMIC REVIEW, 2023)
The global security environment is marked by two converging processes: privatization and militarization, which with different dynamics, scope, intensity and method reconfigure recent security policies, strategic agendas, scientific and research approaches, but also the practice of security itself. The widely accepted privatization of security, in addition to the reduction and fragmentation of the state’s monopoly of force in this area, enables the introduction of non-state actors that independently or in cooperation with traditional state bodies perform an increasing number of security tasks. Therefore, public-private cooperation in the field of security arises as a result of globalist efforts to reduce the influence of the national state in the field of security, while at the same time opening space for the introduction of the private sector to which the state will precisely define through the normative framework and then entrust the performance of a whole series of tasks that were previously traditionally performed exclusively by state bodies. However, when performing security tasks by a public or private actor, risks often arise that require continuous monitoring and then management, i.e. the existence and formalization of a risk management strategy as well as accompanying methodologies and finally defining or determining a whole spectrum of tools, instruments and means for overcoming, not only current but also evolving, convergent and especially systemic risks. From the perspective of the proliferation of numerous strategies and methodologies for preventing, mitigating or remediating risks in this area, special attention will be paid in the paper to new risks that arise due to the extreme complexity, uncertainty and unpredictability of atropocent and climate risks and their impact on the field of security, including their reflections on the cooperation of the public-private sector in the field of security.